Behavior of piles and indolbutyric or homeopathic prepared acid Arnica montana spread of false-erica - Darcieli Aparecida Cassol; Marcelo Dotto; Kelli Pirola; Américo Wagner Júnior (Ornamental Horticulture, 2017)
The market for flowers and ornamental plants is growing. Since the false-érica (Cuphea gracilis) is a plant with many uses in the landscape, adapting to partial shade or full sun can be used for ground covers or chromatic combinations with other plants. Usually, the false-erica is propagated by seeds or by cuttings. The objective of this study was to evaluate the size of stakes and the concentration of IBA (indole butyric acid) and prepared homeopathic base of Arnica montana in rooting false-erica stakes. The collection of cuttings was carried out in arrays plants grown in gardens in standard sizes 6 and 12 cm in length, and were treated with IBA at concentrations of 0; 1.000 and 2.000 mg L-1 in addition to the homeopathic preparation A. montana 12 CH. The experiment was conducted in a completely randomized design in a 2x4 factorial [length x stake stimulant treatment], with 4 replications of 10 cuttings per plot. After 45 days, they were evaluated percentage of rooted and dead cuttings, root length (cm), number of shoots and number of leaves. The concentrations of AIB, and the application of homeopathy stimulated the adventitious rooting processes of this kind.